Dynamic Coordination and Bankruptcy Regulations - Zhong, Hongda; Zhou, Zhen (Review of Financial Studies, 2026)
Many regulations aim to promote coordination among creditors in bankruptcy by ex post restricting their ability to exit distressed firms. However, such restrictions may harm creditors’ ex ante incentives to stay invested, thereby worsening coordination outcomes. We build a dynamic coordination model to show how this force shapes creditor runs, bankruptcy filings, and regulation designs. Intriguingly, filing for bankruptcy early, thereby preserving more assets for latecomers, can prolong firm life. Furthermore, regulators’ clawbacks on prebankruptcy repayments can be superior to firms’ commitment to early bankruptcy filing. Our analysis generates implications for automatic stay, avoidable preference, bank failures, and seniority structure.